The impact of a two-phase diesel fuel pilot injection on the compressed natural gas air–fuel mixture combustion process in a diesel engine - Ilves, Risto; Põldaru, Rauno; Annuk, Andres; Olt, Jüri (Transport, 2022)
Nowadays, there is a global trend towards the use of alternative fuels in order to reduce environmental pollution. For example, Compressed Natural Gas (CNG) has become more widely used around the world. The use of different fuels in engines affects the combustion process and efficiency, with the latter potentially being reduced by such means as, for example, the use of gaseous fuels in conventional diesel engines. Therefore, it is also important to know how CNG combusts in a diesel engine and how the combustion process can be improved. Consequently, the aim of the study is to give an overview of the effect of divided Diesel Fuel (DF) pilot injection on the combustion process of a naturally aspirated diesel engine using dual-fuel mode, with one fuel being DF and the other CNG. The focus of the article is on the commonly used engines on which the diesel injection system works regularly, and CNG fuel is injected into the intake manifold as an additional fuel. The engine DF quantity and injection timing are regulated by the acceleration pedal. The article provides an overview of the diesel and dual-fuel combustion process, and compare the DF and dual-fuel combustion processes. For this purpose, a test was carried out in order to measure the various involved parameters, such as the combustion pressure, torque, and fuel consumption. The results demonstrated that ignition delay does not significantly vary with the use of gas as a fuel source, and the maximum combustion pressure is actually higher with gas. The combustion is more rapid in dual-fuel mode and results indicate that when using dual-fuel mode on regular engines, it would be necessary to regulate the pre- and main-injection timing.